(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Rheumatoid arthritis is a disease that can develop rapidly and cause damage to the musculoskeletal system and even disability.In 80% of patients, destructive processes begin in the joints in the 3-6 months of the onset of the disease, and by the 2nd year of the onset of the disease, erosive processes are detected in the joints. Rehabilitation measures in RP disease prevent destructive processes in the joints.